Efficiency of common filters for water treatment in Tanzania - Komba, Faraja Evod (2023)
Water is very important to all organisms where it acts as the main solvent to many substances and essential for the existence and development of life. According to World Health Organization (2017), inadequate sanitation is a major source of sickness in the world. UN (2017) affirmed that about 90% of diarrheal deaths are due to contaminated water, poor sanitation and poor hygiene. A report from joint monitoring program for water supply and sanitation by WHO and UN (2017) revealed that 4.5 billion people lack access to good sanitation. This shows that people are susceptible to waterborne diseases (Sullivan et al. 2017; Kilungo et al. 2018; Mukaratirwa-Muchayenyereyi et al. 2020). Additionally, the UN report released in 2019 indicated that 2.1 billion people throughout the world still lack access to clean drinking water. As a result, 2.2 million people die each year from waterborne diseases of whom majority of them are children under the age of five years (UN 2019). Aside from the human cost, the World Bank estimated that lack of access to safe water and good sanitation costs the global economy about $ 260 billion per annum (WHO 2017). Therefore, water has been a great issue to be considered all over the world and the various strategies should be envisaged to ensure equitable access to clean and safe water (Ajibade et al. 2014; Ugya et al. 2018).